Symbols that unite command respect - Abd Razak, Dzulkifli (2007)
THERE is every reason to be thankful for the progress and development Malaysia has gone through in the last five decades. But the struggle must continue. Merdeka is one long process that cannot stop. It is like a neverending relay where each generation must take turns to safeguard the nation's independence. This could be in any form and it must build and strengthen what we already have. For someone like New Straits Times columnist Brian Yap, it may be about "springcleaning" when he wrote: "As we commemorate the 50th year since Malaya gained independence, it is high time we cleaned house, too." To him, it is a comforting ritual that he indulges to clear mind. Throwing things that are no longer needed, organising things and finding out what's not done. What things can be given away or requiring redecoration.